Struktur Organisasi Dan Kinerja Pegawai Dalam Perspektif Gender Di UIN Raden Intan Lampung - Masykuroh, Siti; Wakhid, Ali Abdul (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to determine the differences in the organizational structure of Raden Intan Lampung's UIN with a gender perspective so that organizational structures that accommodate women's and men's ASN participation are realized, without differences and know the differences in women's ASN performance in producing good employee performance with a sample of 32 employees taken by proportional random sampling technique. The results of the analysis of this study indicate that there are differences in employee performance between male employees and female employees, based on the calculation of t-test results obtained t = 4,266 with sig. 0,048 (p <0,05), the performance of female employees has an average value amounting to 90.07 compared to 80.06 male employees.